Teaching clinical reasoning to medical students: A brief report of case-based clinical reasoning approach - Mostafa Alavi-Moghaddam; Arman Zeinaddini-Meymand; Soleiman Ahmadi; Aryan Shirani (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Case-based clinical reasoning (CBCR) is the proposed method to improve clinical reasoning. This brief report aimed to evaluate CBCR effectiveness to improve clinical reasoning via an online course. SETTINGS AND DESIGN: This study is a brief report of a before-after quasi-experimental study to evaluate CBCR in medical students of Shahid Beheshti University of Medical Sciences. MATERIALS AND METHODS: Ten online weekly 2-hour sessions of CBCR presentations were instructed to medical students. Each session started with an illness script, and then, the instructor posed the students' five clinical questions in five steps according to the CBCR approach. The clinical reasoning ability of students was evaluated before and 2 weeks after the online courses using four types of standard clinical questions. STATISTICAL ANALYSIS USED: A Wilcoxon signed-rank test was used to assess the difference between pretest and posttest examination scores. RESULTS: This brief report revealed that twenty-one medical students participated in all ten sessions of the CBCR online course and were evaluated in pretest and posttest examinations. A significant improvement in the clinical reasoning total scores in the posttest examination compared with the pretest examination was observed (P = 0.001). In terms of specific types of clinical questions, the mean posttest scores for clinical reasoning problem (CRP) and key feature (KF) examinations were higher than the pretest scores (P = 0.001 and P = 0.005, respectively). CONCLUSIONS: Applying the CBCR approach improved the total clinical reasoning score of medical students during the course. Further studies are needed to evaluate whether this improvement would persist in workplace settings or not.